Social Economic Analysis of Tumbuan Village, Seluma District Due To The Existence of PT. Agrindo Indah Persada Bengkulu - Lovita Lovita; Evi Andriani; Rika Dwi Yulihartika (UNIVED Press, Universitas Dehasen Bengkulu, 2021)
The purpose of this study is to determine the impact of the existence of PT.Agrindo Indah Persada on the socio-economic conditions of the community and to determine the amount of community acceptance as an impact of the existence of PT. Agrindo Indah Persada in Tumbuan Village, Lubuk Sandi District, Seluma Regency. The research location was determined purposively at PT. Agrindo Indah Persada in Tumbuan Village, Lubuk Sandi District, Seluma Regency. The research method used is descriptive and acceptance analysis. The sample of research respondents was 91 people. The results showed the impact of the existence of PT. Agrindo Indah Persada regarding the socio-economic conditions of the community in Tumbuan Village, Lubuk Sandi District, Seluma Regency are (1) Increasing community education, (2) Land Change Function, (3) Environment or land becomes damaged, (4) Increasing Conflict in the Community (5) Reduced interaction between communities (6) Increased facilities and infrastructure (7) Community lifestyle becomes consumptive (8) Increase community livelihoods, (9) Increase income. The average community acceptance in Tumbuan Village, Lubuk Sandi District, Seluma Regency with the presence of PT. Agrindo Indah Persada Rp. 2,897,802.